Conscientious objection in healthcare, referral and the military analogy - Clarke, S (BMJ, 2016)
An analogy is sometimes drawn between the proper treatment of conscientious objectors in healthcare and in military contexts. In this paper, I consider an aspect of this analogy that has not, to my knowledge, been considered in debates about conscientious objection in healthcare. In the USA and elsewhere, tribunals have been tasked with the responsibility of recommending particular forms of alternative service for conscientious objectors. Military conscripts who have a conscientious objection to active military service, and whose objections are deemed acceptable, are required either to serve the military in a non-combat role, or assigned some form of community service that does not contribute to the effectiveness of the military. I argue that consideration of the role that military tribunals have played in determining the appropriate form of alternative service for conscripts who are conscientious objectors can help us to understand how conscientious objectors in healthcare ought to be treated. Additionally, I show that it helps us to address the vexed issue of whether or not conscientious objectors who refuse to provide a service requested by a patient should be required to refer that patient to another healthcare professional.